(untitled) (Research, Society and Development, 2022)
Throughout the pandemic of COVID-19, medical students have been undergoing online learning, which has the potential to cause them anxiety. The study’s objective is to determine a relationship between anxiety scales and gender, year of study, resilience scale, and social support scale. This study used a cross-sectional approach with analytic observational methodology. The year of study and gender were in the biodata section, the resilience scale was calculated utilizing the Nicholson McBride Resilience Questionnaire (NMRQ), and the social support scale was calculated utilizing the Oslo Social Support Scale-3 (OSSS-3). The Beck Anxiety Inventory (BAI) was employed to evaluate anxiety scales. The data was examined utilizing univariate and bivariate methods such as Chi-square and Kendall-tau. The amount of respondents was 238 respondents who were selected by simple random sampling. The result showed significant results (p<0.05) for factors that consist of gender (r=0.183, p<0.01), year of study (r= -0.151, p<0.05), resilience (r= -0.297, p<0.01) and social support (r= -0.243,p<0.01). This research’s findings are gender, year of study, resilience, and social support all have a significant correlation with anxiety scale experienced by respondents while participating in online learning.